The Al-Sail dalam Tinjuan Al-Qur’an Tafsir (Suatu Kajian Tahlīlī Terhadap QS. Al-Zariyat/51:19) - Armimin; Rabiatul Adawiyah; Yuzhril (CV Kalimasada Group, 2025)
This paper examines the essential meaning of the word al-sā’il, which appears in several verses of the Qur’an. Fundamentally, this word means “to ask” or “to beg,” and in the Qur’anic context it can refer to requests of a material, non-material (informational), or combined nature. In surah al-Żāriyāt (51:19), al-sā’il is interpreted as a material beggar, which in modern terms corresponds to a pauper or beggar. This research employs a qualitative method with a descriptive-analytical type of library research. The collected data are organized, processed, and analyzed through exegetical, social, economic, and psychological approaches. The findings indicate three main points: first, al-saā’il denotes a material beggar; second, the meaning relates to individuals in economic hardship or those requesting on behalf of communal needs; and third, the verse emphasizes obligatory rights that should be fulfilled through charity (ṣadaqah), alms (infāq), or gifts. This study is expected to foster empathy and understanding toward beggars as fellow human beings who possess rights clearly affirmed in the Qur’an